Cue-induced Behavioral and Neural Changes among Excessive Internet Gamers and Possible Application of Cue Exposure Therapy to Internet Gaming Disorder - Zhang, Yongjun; Ndasauka, Yamikani; Hou, Juan; Chen, Jiawen; Yang, Li zhuang; Wang, Ying; Han, Long; Bu, Junjie; Zhang, Peng; Zhou, Yifeng; Zhang, Xiaochu (Frontiers in Psychology, 2016)
Internet gaming disorder (IGD) may lead to many negative consequences in everyday life, yet there is currently no effective treatment for IGD. Cue-reactivity paradigm is commonly used to evaluate craving for substance, food, and gambling; cue exposure therapy (CET) is applied to treating substance use disorders (SUDs) and some other psychological disorders such as pathological gambling (PG). However, no study has explored CET’s application to the treatment of IGD except two articles having implied that cues’ exposure may have therapeutic effect on IGD. This paper reviews studies on cue-induced behavioral and neural changes in excessive Internet gamers, indicating that behavioral and neural mechanisms of IGD mostly overlap with those of SUD. The CET’s effects in the treatment of SUDs and PG are also reviewed. We finally propose an optimized CET paradigm, which future studies should consider and investigate as a probable treatment of IGD.